1988
DOI: 10.1136/jcp.41.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of nitroimidazole resistance in Campylobacter pylori by coadministration of colloidal bismuth subcitrate: clinical and in vitro studies.

Abstract: SUMMARY One hundred patients with duodenal ulceration and Campylobacter pylori in their stomach were entered into a double blind placebo controlled prospective study. Treatment schedules were cimetidine and placebo, or cimetidine and tinidazole, or colloidal bismuth subcitrate (CBS) and placebo, or CBS and tinidazole. Seventeen per cent of isolates of C pylori obtained at the first endoscopy were resistant to tinidazole and 70% of the second isolates from patients given cimetidine and tinidazole became tinidaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(82 citation statements)
references
References 10 publications
2
78
0
2
Order By: Relevance
“…11,12 Primary and acquired resistance to antibiotics is an important factor in treatment failure, resulting in an altered cure rate. 12,13 The purposes of the present study were (i) to assess the susceptibility of H. pylori isolates in Japan to MNZ, CLAR and AMOX, (ii) to examine the in¯uence of primary antibiotic resistance to H. pylori treatment, and (iii) to evaluate the prevalence of acquired antibiotic resistance in H. pylori treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Primary and acquired resistance to antibiotics is an important factor in treatment failure, resulting in an altered cure rate. 12,13 The purposes of the present study were (i) to assess the susceptibility of H. pylori isolates in Japan to MNZ, CLAR and AMOX, (ii) to examine the in¯uence of primary antibiotic resistance to H. pylori treatment, and (iii) to evaluate the prevalence of acquired antibiotic resistance in H. pylori treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…18 Bismuth preparations have an effective topical action which can markedly reduce the bacterial load and then favour the elimination of the remaining organisms by the associated antibiotics. 19 There is also evidence that the use of bismuth may prevent the development of acquired resistance to nitroimidazoles 20 and, in vitro, ranitidine bismuth citrate has been shown to signi®cantly reduce the emergence of H. pylori strains spontaneously resistant to metronidazole and clarithromycin. 21 These features may be of help in overcoming the major disadvantage of triple therapies containing both nitroimidazoles and clarithromycin, which are the two antibiotics most frequently shown to develop H. pylori resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Osato et al had shown a synergy between RBC and clarithromycin with a decrease of RBC minimal inhibitory concentrations (MICs) from more than 8 mg/L to less than 2 mg/L in 8 of 10 clarithromycin-resistant Hp strains (26). RBC can release bismuth, which has also been shown to have moderate anti-Hp activity in the gastric mucosa (27). The level of bismuth concentration achieved in the mucosa is very important and markedly higher than the MIC.…”
Section: Discussionmentioning
confidence: 99%